Factors Influencing Teacher Organizational Citizenship Behavior: A Literature Review - Sumiati, Wiwin; Rini, Riswanti; Sucitra, Diah Ayu; Hariri, Hasan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Education provides the opportunity to gain skills that will improve one's quality of life in the future. This research discusses teacher Organizational Citizenship Behavior (OCB) which has an important role in achieving school goals and improving the quality of education. Teachers with high OCB tend to take actions that support school progress and development. The aim of this research is to identify factors that influence teacher OCB based on a literature review. The method used in this research is a literature review by analyzing 33 national and international articles published between 2019 and 2024, obtained via Google Scholar. Data collection was carried out by selecting relevant and high quality articles regarding teacher OCB. The data collected was then analyzed to find factors that influence OCB in teachers. The results of the analysis show that the factors that influence teacher OCB include transformational leadership, job satisfaction, organizational commitment, organizational culture, work motivation, and work discipline. This research found that these factors are interconnected and have a positive impact on increasing teacher OCB. The conclusion of this research is that improving these factors can significantly influence teacher OCB, which in turn can improve the quality of education and achievement of school goals. It is expected that this research can become a reference for further research related to teacher OCB.